OPEN GASTROTOMY APPROACH FOR GASTROINTESTINAL FOREIGN BODIES IN CANINES - Ngakan Nyoman Cahaya Adi; I Gusti Agung Gde Putra Pemayun; I Wayan Gorda (Buletin Veteriner Udayana, 2025)
Gastrotomy is a surgical procedure involving temporary opening of the stomach to remove foreign bodies, typically performed via exploratory laparotomy. An 8-month-old, 5.5 kg female mixed-breed dog was presented after ingesting a foreign object during play. The owner observed the dog for three days with no spontaneous elimination through feces or vomiting. Clinical examination revealed normal vital parameters and no signs of gastrointestinal distress. Abdominal radiography identified a round, radiopaque foreign body retained in the gastric lumen. The case was diagnosed as gastric foreign body (corpus alienum) ingestion. Surgical intervention via laparotomy-assisted gastrotomy successfully removed the marble-like object. Postoperative management included intravenous cefotaxime (20 mg/kg BID for 3 days), transitioned to oral cefixime (10 mg/kg BID for 5 days), and meloxicam analgesia (0.5 mg/kg SID for 5 days). By postoperative day 7, the dog demonstrated normal appetite, elimination patterns, and complete wound healing. This case highlights the importance of prompt veterinary intervention for young dogs exhibiting pica behavior, particularly when gastrointestinal signs (vomiting, diarrhea, or anorexia) are observed, to prevent complications from foreign body ingestion.